REPRESENTASI KERAGAMAN BUDAYA DALAM FILM KARTUN UPIN DAN IPIN : PEMAHAMAN LINTAS BUDAYA - Andriani, Viena Wanidha (INCARE, International Journal of Educational Resources, 2021)
The construction of cultural diversity in the film “Upin dan Ipin” is very interesting to be analyzed. This research is a cross-cultural understanding research with qualitative approach. The data is taken by internet acces in youtube channel. By applying Hall’s representation theory, this research wants to examine how the representation of cultural diversity is constructed in the film. This research also reveals how the cross-cultural understanding is displayed in the film and what ideology the writer or filmmaker wants to convey to the public, especially children. The results of this study show that the cultural diversity is not only represented through traditional language and clothing, but also traditional parties, arts, and typical foods of each culture. The cultural diversity displayed is the culture of India, China and Malaysia. In cross-cultural understanding, the attitude values ​​are shown through greeting of the Chinese called "Pai" or "Soja" and greeting of the Indian or "Namaste". The ideology that the filmmaker wants to convey to the public, especially children, is how cultural diversity should be addressed with full awareness and tolerance to build the unity and create a harmonious life to avoid conflicts between the individuals or community.